GE_GERICHTE C/5065/2018 vom 26. Februar 2019 - GE Cour de justice (2019)
HYPOTHÈQUE LÉGALE DES ARTISANS ET ENTREPRENEURS ; INTÉRÊT DIGNE DE PROTECTION ; PÉREMPTION | CPC.59.al1; CPC.59.al2.leta; CC.837.al1.ch3; CC.972.al1; CC.839.al2